On the invertibility of differential operators of the second order - Baskakov, A. G.; Chernyshov, M. K. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We present sufficient conditions for the invertibility of a second-order differential operator with variable coefficients in the space Lp.